2016
DOI: 10.1039/c6ce02005d
|View full text |Cite
|
Sign up to set email alerts
|

The role of PLLA-g-montmorillonite nanohybrids in the acceleration of the crystallization rate of a commercial PLA

Abstract: Employing the hydroxyl groups on the surface of Cloisite® 30B montmorillonite (Cl30B), the ring-opening polymerization of L-lactide was performed with a metal-free catalyst to yield a PLLA-g-Cl30B nanohybrid with low M n grafted PLLA chains (i.e., 9 kg mol −1 ). This nanohybrid was then melt mixed with PLA 4032D from NatureWorks, which is a slow-crystallizing PLA as it contains 2% D-isomers and has a high M n value (i.e., 123 kg mol −1 ). The samples were characterized by TEM, WAXS, SAXS, DSC and Polarized Lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…Moreover, a small amount of d ‐lactic acid in the PLA seriously slows down the crystallization process. As a result, the neat PLA showed almost no crystallization peak upon cooling and no significant melting peak, as observed in Figure ; this was consistent with the experimental results of Li and Huneault and Zaldua et al . After the addition of a small amount of TPU, a sharp crystal peak and wide melting peak occurred; this indicated that the flexible chains of TPU were conducive to improving the kinetic capability and accelerating the crystal growth of PLA.…”
Section: Resultssupporting
confidence: 89%
“…Moreover, a small amount of d ‐lactic acid in the PLA seriously slows down the crystallization process. As a result, the neat PLA showed almost no crystallization peak upon cooling and no significant melting peak, as observed in Figure ; this was consistent with the experimental results of Li and Huneault and Zaldua et al . After the addition of a small amount of TPU, a sharp crystal peak and wide melting peak occurred; this indicated that the flexible chains of TPU were conducive to improving the kinetic capability and accelerating the crystal growth of PLA.…”
Section: Resultssupporting
confidence: 89%
“…Moreover, the OMMT lamellas were dispersed in PLA matrix well, more nucleation sites formed that contributed to give a high degree of overall crystallinity (X c ). At >3.0 wt % OMMT, the effect of aggregation of nanoclay was enhanced and the number of nucleation sites decreased, which was consistent with the XRD results.…”
Section: Resultssupporting
confidence: 88%
“…In order to calculate the value of the lamellar thickness (l), we have employed the approximation l = Xv L, where Xv is the crystal volume fraction (see the Supporting Information for the procedure employed to calculate the crystal volume fractions). 62 Using the lamellar thickness values and the experimental melting points of the isothermally crystallized samples, the Thompson-Gibbs equation can be applied. 59 Therefore, 0 is higher in cyclic PLAs than in their linear analogues and D or L stereoregularity has no influence on this thermal property.…”
Section: Fitting Of Dsc Isothermal Data To the Avrami Modelmentioning
confidence: 99%